Safe Finger Tourniquet—Ideas. (March 2016) - Wei, Lin-Gwei; Chen, Chieh-Feng; Hwang, Chun-Yuan; Chang, Chiung-Wen; Chiu, Wen-Kuan; Li, Chun-Chang; Wang, Hsian-Jenn
Abstract : Abstract: Tourniquets are often needed for optimized phalangeal surgeries. However, few surgeons forget to remove them and caused ischemic injuries. We have a modified method to create a safe finger tourniquet for short duration finger surgeries, which can avoid such tragedy. It is done by donning a glove, cutting the tip of the glove over the finger of interest, and rolling the glove finger to the base. From 2010 to 2013, approximately 54 patients underwent digital surgical procedures with our safe finger tourniquet. Because the glove cannot be forgotten to be removed, the tourniquet must be released and removed. This is a simple and efficient way to apply a safe finger tourniquet by using hand rubber glove for a short-term bloodless finger surgery and can achieve an excellent surgical result.